Political Law of The Government in A Special Naturalization of Indonesian Football Players Based on Walfare State Theory - Muhammad Zulhidayat; Atma Suganda; Imran Bukhari Razif (Green Publisher Indonesia, 2022)
The naturalization process itself is known in Law no. 12 of 2006 concerning Citizenship of the Republic of Indonesia, naturalization is divided into two, namely ordinary naturalization and special naturalization, ordinary naturalization is sufficient to meet the administrative requirements stipulated by law, while special naturalization must obtain the consideration of the House of Representatives before obtaining citizenship. The thing that needs to be observed in this special naturalization process is that someone who wants to be naturalized must first have service to the Indonesian nation, the anomaly that is happening at this time is that the government allows naturalization policies without considering the interests of the state, but for the interests of clubs playing in Indonesian leagues. . Therefore, this study takes the formulation of the problem, how is the legal politics of the special naturalization policy for football players in Indonesia in terms of Law no. 12 of 2006 concerning Citizenship? In this study, the research method is normative juridical. The conclusion in this study is that the current naturalization policy is contrary to the constitutional mandate, especially in Article 20 of Law No. 12 of 2006 concerning citizenship, by facilitating the naturalization process, making naturalization players filled with players whoThe naturalization process itself is known in Law no. 12 of 2006 concerning Citizenship of the Republic of Indonesia, naturalization is divided into two, namely ordinary naturalization and special naturalization, ordinary naturalization is sufficient to meet the administrative requirements stipulated by law, while special naturalization must obtain the consideration of the House of Representatives before obtaining citizenship. The thing that needs to be observed in this special naturalization process is that someone who wants to be naturalized must first have service to the Indonesian nation, the anomaly that is happening at this time is that the government allows naturalization policies without considering the interests of the state, but for the interests of clubs playing in Indonesian leagues. . Therefore, this study takes the formulation of the problem, how is the legal politics of the special naturalization policy for football players in Indonesia in terms of Law no. 12 of 2006 concerning Citizenship? In this study, the research method is normative juridical. The conclusion in this study is that the current naturalization policy is contrary to the constitutional mandate, especially in Article 20 of Law No. 12 of 2006 concerning citizenship, by facilitating the naturalization process, making naturalization players filled with players who are of old age and cannot contribute to the Indonesian national team for a long time.